2001
DOI: 10.1590/s0100-879x2001000300015
|View full text |Cite
|
Sign up to set email alerts
|

Acute phenobarbital administration induces hyperalgesia: pharmacological evidence for the involvement of supraspinal GABA-A receptors

Abstract: The aim of the present study was to determine if phenobarbital affects the nociception threshold. Systemic (1-20 mg/kg) phenobarbital administration dose dependently induced hyperalgesia in the tail-flick, hot-plate and formalin tests in rats and in the abdominal constriction test in mice. Formalin and abdominal constriction tests were the most sensitive procedures for the detection of hyperalgesia in response to phenobarbital compared with the tail-flick and hot-plate tests. The hyperalgesia induced by system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…However, it has also been reported that systemic administration of non-hypnotic doses of ethanol and barbiturates to rats results in reduction of tail-flick latency and this is abolished by non-convulsant doses of the GABA A receptor channel blocker picrotoxin, indicating involvement of GABAergic mechanisms in the mediation of ethanol-induced hyperalgesia [22]. Other studies have demonstrated that intracerebroventricular, but not intrathecal administration of these drugs induces a similar hyperalgesic state that is also reversed by a GABA A receptor blocker [45,46]. These results suggested that ethanol and some barbiturates might induce pain hypersensitivity (hyperalgesia) through acting on GABA A receptors at the supraspinal level, while they induce antinociception (analgesia) through acting on GABA A receptors at the spinal level.…”
Section: Where and How Ethanol Modulates Pain?mentioning
confidence: 92%
“…However, it has also been reported that systemic administration of non-hypnotic doses of ethanol and barbiturates to rats results in reduction of tail-flick latency and this is abolished by non-convulsant doses of the GABA A receptor channel blocker picrotoxin, indicating involvement of GABAergic mechanisms in the mediation of ethanol-induced hyperalgesia [22]. Other studies have demonstrated that intracerebroventricular, but not intrathecal administration of these drugs induces a similar hyperalgesic state that is also reversed by a GABA A receptor blocker [45,46]. These results suggested that ethanol and some barbiturates might induce pain hypersensitivity (hyperalgesia) through acting on GABA A receptors at the supraspinal level, while they induce antinociception (analgesia) through acting on GABA A receptors at the spinal level.…”
Section: Where and How Ethanol Modulates Pain?mentioning
confidence: 92%
“…PB may directly activate the GABA A receptor [96]. The actions of PB through these effects may reduce anxiety, promote sleep, induce general anesthesia, and act as an effective control of generalized and partial tonic–clonic seizures [97,98]. PB was the World Health Organization’s first-line AED in developing countries because of its low cost and effectiveness in the treatment of seizures.…”
Section: Introductionmentioning
confidence: 99%
“…By suppressing descending inhibitory systems, pentobarbital may facilitate central sensitization and the development of pain after nociceptive input. Supporting this, others showed that barbiturates can induce enhanced pain (hyperalgesia) on a number of measures (Franklin and Abbott 1993;Yokoro et al 2001). This hyperalgesia may result from changes in dorsal horn neurons, which change response profiles to noxious stimuli from low threshold to wide dynamic range neurons after pentobarbital administration in intact animals (Collins and Ren 1987).…”
Section: Discussionmentioning
confidence: 87%